Ovarian dysgerminoma: a case report - Wakode, Shamrao Ramji; Bhat, Varsha Narayana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
An ovarian dysgerminoma is a rare, malignant tumour occurring in young women, accounting for 1% to 2% of all primary ovarian neoplasms. A 22 years old female presented with 6 months of amenorrhea and lump in the abdomen. Her physical examination was remarkable with 36 weeks sized huge abdominal mass. Subsequent computed tomography revealed 22×23×32.4 cm mixed density lesion in pelvi-abdominal region and multiple paraaortic and mesenteric lymph node with gross pleural effusion. On further evaluation raised beta-hcG and LDH were noted and hence dysgerminoma was suspected. Total abdominal hysterectomy with right salpingo-ophorectomy with resection of tumour mass with partial omentectomy and lymphadenectomy was performed. Histopathology reports were suggestive of dysgerminoma.